Educational Culture within the Families of School Dropouts in Bandung City - Sanny Marlem; Erna Herawati (Labor Jurusan Sosiologi Fakultas Ilmu Sosial Universitas Negeri Padang, 2026)
Research on children who have dropped out of school has largely focused on economic factors and access to education, while the dimension of educational culture within families remains relatively understudied, particularly in urban contexts. This study aims to examine how educational culture is understood within the families of children who have dropped out of school and how such understandings influence educational continuation and discontinuation. Using a qualitative ethnographic approach, data were collected through observations and in-depth interviews with 25 participants consisting of school dropout children and their family members in several areas of Bandung City. Drawing on the anthropology of education and Pierre Bourdieu’s concept of forms of capital, the study found that families continued to regard education as important and actively instilled educational values in their children. However, education was often understood pragmatically as a means of securing employment and improving the family’s economic condition. In some cases, working at a young age was considered more realistic than continuing schooling because it provided immediate income. Furthermore, economic constraints, negative academic experiences, and psychological pressures led some children and families to no longer prioritize schooling. The findings reveal that school dropout may occur even when education is valued, as educational aspirations are continuously negotiated against everyday needs, school experiences, and socio-economic pressures. These findings highlight the need for policies that focus not only on financial assistance but also on psychosocial support and culturally informed approaches.